Penser sa santé en travaillant en 12 heures - Fanny Vincent (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article takes an interest in the representations of their health of nurses and nurses’ aides working 12 hours shift in the public hospital. It takes as a starting point the results of classical researches that study “risks” of work according to the majority risk of each occupation (repetitive stress injuries for nurses’ aides and psychosocial disorders for nurses). Based on speeches of nurses and nurses’ aides working 12 hours shift in public hospital, the article questions the gap or the permeability between these two categories. It shows that the way nurses and nurses’ aides consider their health and the way they accept or not the impacts of work on their health depends on their relationship to work. This is also appreciated from the point of the organization of their life. All along, the article shows that thinking together physical and mental pressures of the work is heuristic to understand the place of work for nurses and nurses’ aides.